2008
DOI: 10.3174/ajnr.a0793
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications of Arteriovenous Malformation Embolization Using Liquid Embolic Agents

Abstract: BACKGROUND AND PURPOSE:Embolization of arteriovenous malformations (AVMs) is commonly used to achieve nidal volume reduction before microsurgical resection or stereotactic radiosurgery. The purpose of this study was to examine the overall neurologic complication rate in patients undergoing AVM embolization and analyze the factors that may determine increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 19 publications
2
60
0
2
Order By: Relevance
“…Recent studies reported morbidity ranging from 3-11%, and mortality from 0 -4%, 2,4,5,7,8,11,[19][20][21][22][23][24][25][26] with associations to angioarchitecture, embolic agents, microcatheters, and the manipulator's skills. Studies on different embolization materials, such as silk, 24 polyvinyl alcohol (PVA) and coil, 25 Onyx, 11 and n-BCA, 23 showed 1.4%, 13%, 19.5%, and 50% rates for morbidity and 0%, 0%, 2.9%, and 1.9% for rates of mortality, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported morbidity ranging from 3-11%, and mortality from 0 -4%, 2,4,5,7,8,11,[19][20][21][22][23][24][25][26] with associations to angioarchitecture, embolic agents, microcatheters, and the manipulator's skills. Studies on different embolization materials, such as silk, 24 polyvinyl alcohol (PVA) and coil, 25 Onyx, 11 and n-BCA, 23 showed 1.4%, 13%, 19.5%, and 50% rates for morbidity and 0%, 0%, 2.9%, and 1.9% for rates of mortality, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,7,8 However, although the overall cure rates in these series have varied, none have demonstrated cure for most of their patients (Table). In addition, the permanent disabling morbidity or mortality rates have been higher than those in several recent large series using predominantly or exclusively n-BCA, [9][10][11][12] which have ranged from 1.6% to 6.5%. Embolization for cure was not the primary aim in most patients treated in these series.…”
mentioning
confidence: 73%
“…Additional treatment goals may include staged reduction of blood flow in an AVM by stepwise occlusion of deep feeding arteries that could provide dose planning to more critical locations (14,(17)(18)(19)22). …”
Section: █ Discussionmentioning
confidence: 99%